Value judgment in war for the planet of the apes movie: a literature study - Sedayatana, I Wayan Arya Jaya; Santika, I Dewa Ayu Devi Maharani; Winarta, Ida Bagus Gede Nova (Institut Pariwisata dan Bisnis Internasional, 2022)
According to Trusted (1987), Moral judgment is verbally embodied in statement, sentences that assert that something or is not the case that can therefore be true or false. It can be found in the movie in many genres especially when there are conflicts in the movie. This study concerns with the analysis of one of the moral judgment types: Value Judgment. The data taken from War for the Planet of the Apes movie and they are collected through observation and note taking technique. The theory of Trusted (1987) is used to analyse the value judgment type. The result shows that there are some values judgments appear in the movie and are uttered not just by the main character, but also the other characters in the movie.